To the question of knowledge managers’ education - E. Y. Grinberg; A. Y. Pleshkova (Открытое образование (Москва))
The article is devoted to the identification of key features of training specialists in knowledge management and systematization of information sources available to them. The relevance of the subject is related to the growing need for managerial personnel, capable of organizing work with knowledge at the enterprise in order to achieve competitive advantages. The study examined the definitions associated with the management of knowledge in the foreign and domestic literature, analyzed the number of subjects taught in Russian specialized universities, revealed the predominance of non-formal education over education in universities. The phenomenon of teaching knowledge management within the framework of such related disciplines as information technology and personnel management has been studied. The article also systematizes the trends in which knowledge management projects are implemented. Based on the above specifics, it is suggested that the main driver of the development of non-formal education in this area is the entrepreneurial initiative of experts. The directions in which the contribution of Russian science to the development of knowledge management as a discipline is manifested to a special extent. Such spheres are the intellectual capital and information technologies.The article is intended for researchers and practitioners whose professional interests lie in the field of knowledge management. In conclusion, ways of improving education systems in higher education institutions and non-formal education are proposed to increase the competence of all specialists who work in the field of knowledge management.